Analisis Standar Penerangan pada Gedung IDB Laboratory FMIPA UNESA Berbasis Visual Basic 6.0 - Muhammad Syafruddin Nur; Subuh Isnur Haryudo; Puput Wanarti Rusimamto; Raden Roro Hapsari Peni Agustin Tjahyaningtijas (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Lighting is a major requirement in human life to be able to see objects around clearly, lighting is obtained from natural light sources and artificial light sources. The IDB laboratory building of the FMIPA UNESA has many rooms with different functions and uses, so the lighting of each room must be adjusted to the Indonesian National Standard (SNI 03-6575-2001). Therefore, a program is needed to analyze and determine the number of lights used quickly and accurately in order to achieve safe and comfortable lighting according to (SNI 03-6575-2001). In this case the method used is to use the calculation of the visual basic 6.0 program by inputting the dimensions of each room, namely length, width, height, and the type of artificial lighting used. Based on the results of the calculation of the lighting standards of the IDB building using the visual basic 6.0 program, it is known that only the prayer room on the 1st floor, the microscope room on the 2nd floor, the warehouse on the 1st, 2nd, 3rd and 4th floors and the microteaching room on the 2nd, 3rd and 4th floors meet SNI 03-6575-2001. Whereas for other rooms such as libraries and laboratories cannot meet SNI 03-6575-2001 so that action needs to be taken so that they can meet the standards, namely by increasing the number of lighting points in each room, or it can also be by replacing the type of lighting with a larger lumen value than before.